The nature of embryonic mosaicism across female age spectrum: an analysis of 21,345 preimplantation genetic testing for aneuploidy cycles - Abigail Armstrong, M.D; Lindsay Kroener, M.D; Jenna Miller, M.S; Anissa Nguyen, M.P.H; Lorna Kwan, M.P.H; Molly Quinn, M.D (Elsevier, 2023)
Objective: To understand how mosaicism varies across patient-specific variables and clinics. Design: Cross-sectional cohort. Setting: Genetic testing laboratory. Patients: A total of 86,208 embryos from 17,366 patients underwent preimplantation genetic testing for aneuploidy using next-generation sequencing. Intervention(s): Mosaic embryos were classified as either low-level (20%-40%) or high-level (40%-80%) and by type of mosaic error: single segmental, complex segmental, single chromosome, or complex abnormal mosaic. The rate of mosaicism was stratified by the Society for Assisted Reproductive Technology age categories: <35 years, 35-37 years, 38-40 years, 41-42 years, and >42 years. Main Outcome Measure(s): Distribution of chromosomal findings and prevalence of mosaicism type by age. Probability of creating mosaic embryos in a subsequent cycle. Result(s): Among all embryos, 44% were euploid, 40.2% were aneuploid, and 15.8% were mosaic. Both low-level and high-level mosaicism were more prevalent among younger patients. Of all mosaic embryos, the youngest age cohort <35 years had the highest proportions of single and complex segmental mosaicism (37.9% and 6.8%, respectively), whereas those aged >42 years had the highest single whole chromosome and complex abnormal mosaicism (37.1% and 34.0%, respectively). Although there was variability in mosaic rates across clinics, the median mosaic rate over 3 years ranged from 14.48% to 17.72%. A diagnosis of a mosaic embryo in a previous cycle did not increase a patient's odds for having a mosaic embryo in a subsequent cycle. Conclusion(s): Mosaicism is overall higher in younger patients, but the complexity of mosaic errors increases with age. A history of mosaicism was not associated with mosaicism in subsequent cycles. Additional research is needed to understand the etiologies of the various subtypes of mosaic embryos and clinical outcomes associated with their transfer.